Alpha-Synuclein Deposition Within Sympathetic Noradrenergic Neurons Is Associated With Myocardial Noradrenergic Deficiency in Neurogenic Orthostatic Hypotension. Issue 4 (April 2019) - Isonaka, Risa; Rosenberg, Avi Z.; Sullivan, Patti; Corrales, Abraham; Holmes, Courtney; Sharabi, Yehonatan; Goldstein, David S.
Abstract : Lewy body diseases involve neurogenic orthostatic hypotension (nOH), cardiac noradrenergic deficiency, and deposition of the protein AS (alpha-synuclein) in sympathetic ganglion tissue. Mechanisms linking these abnormalities are poorly understood. One link may be AS deposition within sympathetic neurons. We validated methodology to quantify AS colocalization with TH (tyrosine hydroxylase), a marker of sympathetic noradrenergic innervation, and assessed associations of AS/TH colocalization with myocardial norepinephrine content and cardiac sympathetic neuroimaging data in nOH. Postmortem sympathetic ganglionic AS/TH colocalization indices and myocardial norepinephrine contents were measured in 4 Lewy body and 3 rare non-Lewy body nOH patients. Sixteen Lewy body and 11 non-Lewy body nOH patients underwent in vivo skin biopsies and thoracic 18 F-dopamine positron emission tomographic scanning, with cutaneous colocalization indices expressed versus cardiac 18 F-dopamine–derived radioactivity. Ganglionic AS/TH colocalization indices were higher and myocardial norepinephrine lower in Lewy body than non-Lewy body nOH ( P =0.0020, P =0.014). The Lewy body nOH group had higher AS/TH colocalization indices in skin biopsies and lower myocardial 18 F-dopamine–derived radioactivity than did the non-Lewy body nOH group ( P <0.0001 each). All Lewy body nOH patients had colocalization indices >1.5 in skin biopsies and 18 F-dopamine–derived radioactivity <6000 nCi-kg/cc-mCi, a combination not seen in non-Lewy body nOH patients ( P <0.0001). In Lewy body nOH, AS deposition in sympathetic noradrenergic nerves is related to postmortem neurochemical and in vivo neuroimaging evidence of myocardial noradrenergic deficiency. These associations raise the possibility that intraneuronal AS deposition plays a pathophysiological role in the myocardial sympathetic neurodegeneration attending Lewy body nOH. Abstract : Supplemental Digital Content is available in the text.